The Digital Route in the Government of Guillermo Lasso: An Analysis Based on Social Networks and Communication Strategies - Encalada Jaramillo, Francisco Gabriel (2023)
This study analyzes the presence or absence of communication strategies managed in the informative publications of Guillermo  Lasso, president of the Republic of Ecuador, from a qualitative approach and a non-probabilistic sampling, a semi-structured interview was conducted with the communication secretary of the presidency between the period 2015 to 2017, and is counteracted with a multimodal matrix to determine the interactions, visual elements and messages published on the social networks of: facebook, Twitter and TikTok, with more than 450 publications analyzed in total, it is evident how the president maintains a business and family discourse, relegating the important aspects that the president of a country must consider, since it does not manage to set a trend but it does become a follower of the conjunctures.